A new species of the Callophrys paulae Pfeiffer, 1932 species group from Afghanistan (Lepidoptera, Lycaenidae) - Krupitsky, Anatoly V.; Pljushtch, Igor G.; Pak, Oleg V. (Zootaxa, 2015)
A new species from the Callophrys paulae Pfeiffer, 1932 species group—C. succuba sp. n.—is described from the mountains of Central Afghanistan, Bamyan Province. The new species differs from the geographically close C. p. jomuda Nekrutenko & Tshikolovets in morphology of the male and female genitalia along with the distinct wavy shape of the postdiscal white line on the hindwing underside. Discovery of the new species from C. paulae species group extends known distribution range of the group to the eastern part of the Iranian Plateau in Central Afghanistan.